Genotypes of pain and analgesia in a randomized trial of irritable bowel syndrome - Vollert, Jan; Wang, Ruisheng; Regis, Stephanie; Yetman, Hailey; Lembo, Anthony J.; Kaptchuk, Ted J.; Cheng, Vivian; Nee, Judy; Iturrino, Johanna; Loscalzo, Joseph; Hall, Kathryn T.; Silvester, Jocelyn A. (Frontiers in psychiatry, 2022)
Background: Irritable bowel syndrome (IBS) is a highly prevalent chronic pain disorder with multiple underlying mechanisms and few treatments that have been demonstrated to be effective in placebo controlled trials. One potential reason may be the use of composite outcomes, such as the IBS Symptom Severity Scale (IBS-SSS) which includes descriptive items related to pain frequency and pain intensity as well as bowel dysfunction and bloating. We investigated if different features of IBS pain have distinct genetic associations and if these may be moderated by sex hormones. Participants and Setting: Adult outpatients with moderately severe IBS (>175 on IBS-SSS) enrolled in a clinical trial reported IBS-SSS at baseline and after 6 weeks of therapy. Methods: Fixed effects modeling was used to test the effect of COMT rs4680 genotype to change in pain severity (rated 0-100) and pain frequency (defined as number of days with pain in the past 10 days) from baseline to week 6 with IBS treatment. Parallel exploratory genome-wide association studies (GWAS) were also performed to identify single nucleotide polymorphisms (SNPs) associated with change in pain severity or pain frequency across all participants. Results: A total of 212 participants (74% female) were included. The COMT rs4680 met allele was associated with decreased pain severity over the course of the trial in gene dosage models [beta(SE) −5.9 (2.6), P = 0.028]. Exploratory GWAS for change in pain frequency identified 5 SNPs in close proximity on chromosome 18 near L3MBTL4 which reached genome-wide significance (all < P 5.0E-8). This effect was not mediated by changing estradiol levels. There was also a region of chromosome 7 with 24 SNPs of genome-wide suggestive significance for change in pain severity (all < P 1.0E-5). Conclusions: Previously reported association between COMT rs4680 genotype and treatment response as measured by IBS-SSS is related to pain severity, but not pain frequency. We also identified new candidate genes associated with changes in IBS pain severity (SNX13) and pain frequency ( L3MBTL4) in response to treatment. Further studies are needed to understand these associations and genetic determinants of different components of IBS-SSS. ClinicalTrials.gov, Identifier: NCT0280224.
Gesehen am 06.05.2024